Urban Agriculture as a Catalyst for Revitalization Processes in Residential Districts of European Cities. The Case of Anderlecht, Roeselare and Romainville - Kleszcz Justyna (Architecture, Civil Engineering, Environment)
The article presented herein constitutes a research summary on urban, multi-purpose facilities that combine commercial, service and industrial functions with the concept of commercial urban agriculture and residential housing, which came into existence in the second decade of the 21st century as one of the forms of revitalization of neglected housing and industrial districts. It aims to support the thesis regarding the catalyzing role of urban agriculture in transforming urban tissue at the touch-point of its various functional zones and its growing role as an element of nature in transforming urban structures. The examination of the selected facilities, catalogued as belonging to the group in scope, provided a subsequent explanation of the problem of diversity and their recently relatively more excellent value in space, especially housing districts. It also allowed us to address the question of their increasing popularity following 2019. The research is based on the method of historical and interpretative mixed research combined with three case studies analysis: Abattoir BIGH in Anderlecht (Belgium), Agrotopia (Inagro) in Roeselare (Belgium) and La Cité Maraîchère in Romainville (France).